Outcome of External Dacryocystorhinostomy with Adjunctive Mitomycin C in Tertiary Care Hospital - Syed Fawad Rizvi, Narain Das, Shakir Zafar, Farhan Amjad Jafri (Pakistan Journal of Ophthalmology, 2016)
Purpose: To evaluate the role of intra-operative mitomycin C in external DCR in cases of recurrent (previously treated medically) and chronic dacryocystitis. Study Design: Interventional case series. Place and Duration of Study: From May 2012 to November 2014 in LRBT free base eye hospital Korangi No. 2½ Karachi, a tertiary care hospital in Pakistan. Material and Methods: 150 patients (males 62, females 88), age of patients ranged from 22 to 56 years were included in the studies. All patients underwent external DCR with intubation with the adjunctive use of topical mitomycin C primarily. All Patients underwent the same surgical procedure performed by two surgeons with average follow up period of 12 months. Success was assessed objectively by irrigation of punctae, with absence of regurgitation, and subjectively by absence of epiphora and discharge. Results: Out of 150 patients, 138 patients (92%) remained symptom free, while 12 patients (8%) complained of persistent watering and discharge despite an uncomplicated